2018
DOI: 10.1590/1983-1447.2018.2017-0095
|View full text |Cite
|
Sign up to set email alerts
|

Percepção do usuário no autocuidado de úlcera em membros inferiores

Abstract: Self-care is the result of dialogue between the user/nurse/health workers and the link they establish when they share care. The support of family members and the service can facilitate or limit care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 7 publications
1
10
0
11
Order By: Relevance
“…A systematic review found that patients with VUs are more likely to be overweight or obese, in addition to having difficulties to reach an ideal BMI, since the pain limits their mobility and leads to changes in their life habits (17) . A Brazilian qualitative study, with a sample of ten patients, found that self-care is a result of the bond between health professionals, patients, and the support of family members, a triad that is essential for the work related to healthcare to be shared (18) . The nurse must monitor, stimulate, and encourage patients and family members to continuously care for the VUs and control the CVI, also encouraging them to adopt healthy habits, which are essential for patients to live with chronic pathologies, and diminish the discomforts related to these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that patients with VUs are more likely to be overweight or obese, in addition to having difficulties to reach an ideal BMI, since the pain limits their mobility and leads to changes in their life habits (17) . A Brazilian qualitative study, with a sample of ten patients, found that self-care is a result of the bond between health professionals, patients, and the support of family members, a triad that is essential for the work related to healthcare to be shared (18) . The nurse must monitor, stimulate, and encourage patients and family members to continuously care for the VUs and control the CVI, also encouraging them to adopt healthy habits, which are essential for patients to live with chronic pathologies, and diminish the discomforts related to these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os dados apresentados neste estudo, a ocorrência de ferida crônica tratada na APS é recorrente, acometendo (19,22,24) .…”
Section: Considerandounclassified
“…Se houver um déficit entre o que o usuário pode fazer e o que precisa ser feito para manter o cuidado da lesão, o enfermeiro será necessário para auxiliar o usuário em suas necessidades de saúde. No caso dos usuários com úlcera em membros inferiores, entende-se que estes conseguem executar ou podem aprender a executar medidas de autocuidado terapêutico, adequando necessidades e atividades de autocuidado (Garcia et al, 2018).…”
Section: Os Cuidados Aos Pacientes Com Feridas Diabéticasunclassified